'Sorry doctor….I didn't hear that….': phenomenological analysis of medical students' experiences of simulated hearing impairment through virtual reality. (27th August 2020) - McLaughlin, Niamh; Rogers, Janet; D'Arcy, John; Gormley, Gerard
Abstract : Introduction: Hearing impairment is a common condition that can have a significant impact on an individual. Ineffective communication between such individuals and doctors remains an important barrier. There is a need to provide medical students with a deeper understanding of such challenges. Increasingly, simulation is being used to develop empathy skills. In this study, we aimed to seek a deep understanding of medical students' experiences of being placed in the role of a hearing-impaired patient by means of a virtual reality (VR) simulation. Methods: A multidisciplinary group developed a 360° VR video-learning experience. This experience portrayed a consultation with a doctor from a hearing-impaired individual's perspective. A qualitative study approach, using hermeneutic phenomenology, was conducted. Following the VR experience, students were interviewed, and transcripts of interviews were analysed using a Template Analysis approach. Results: Analysis yielded four main themes: (1) 'much more than just watching a video': a VR experience of hearing impairment; (2) 'hearing through their ears': experiencing a person's world with hearing impairment; (3) 'not just what you can't hear…but how it makes you feel': reactions evoked by a VR hearing impairment experience and (4) redirecting my future professional self? Discussion: This study provides an insight into medical students' experiences of a novel VR hearing impairment simulation. VR simulation has the potential to provide a novel complementary training method for medical students. By providing an immersive learning experience, VR can offer an empathic stepping into the ears of those that live with hearing impairment.